Aluminum material for high-corrosion-resistance cover plate of new energy lithium battery and preparation method of aluminum material
By selecting the components of aluminum materials and carrying out specific treatments, the microstructure and electrochemical behavior of aluminum materials for lithium battery covers are optimized, and the shortcomings of existing aluminum alloys in corrosion resistance, mechanical strength and electrical conductivity are solved, and high-performance lithium battery covers are achieved.
Patent Information
- Application Number
- CN202510047284.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing aluminum alloy for lithium battery cover plates has shortcomings in corrosion resistance, mechanical strength, impact resistance, low-temperature brittleness and electrical conductivity, which affects the performance, safety and reliability of the battery.
By selecting the component types and compositions of aluminum materials, especially controlling the mass percentage content of Fe, Mn, and Cu to be (1.3-1.5): (0.3-0.4): (0.5-0.6), and carrying out specific homogenization and annealing treatment, the microstructure and electrochemical behavior of aluminum materials are optimized.
It realizes high corrosion resistance, excellent mechanical properties, improved conductivity and enhanced acid corrosion resistance of aluminum materials, and meets the high performance needs of new energy lithium battery covers.
Smart Images

Figure BDA0005238860120000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aluminum materials, and specifically relates to an aluminum material for a new energy lithium battery with high corrosion resistance and a preparation method thereof. Background Art
[0002] Aluminum material for new energy lithium battery cover is one of the key components in lithium battery manufacturing. It not only seals the battery, but also protects the internal battery cells, provides electrical connections, and ensures the safety of the battery. Selecting the right aluminum material is crucial to improving the performance, reliability, and safety of lithium batteries.
[0003] Lithium battery cover plates usually use aluminum alloy as the base material. Common alloy series include 5000 series (such as 5052, 5083) and 6000 series (such as 6061). These alloys have good mechanical strength and processing properties and are suitable for manufacturing complex cover plate structures. However, they also face some technical challenges and problems, which may affect the performance, safety and reliability of the battery: (1) Insufficient corrosion resistance. Although aluminum alloys have certain corrosion resistance, they may still corrode when in contact with the electrolyte inside the lithium battery for a long time, especially when the electrolyte leaks or the internal environment of the battery changes. Corrosion will cause the mechanical strength of the cover plate to decrease, and even cause short circuits or leakage, affecting the safety of the battery. 2. Mechanical strength and toughness. Lithium batteries will produce tiny expansion and contraction during the charging and discharging process. Long-term cyclic use may cause fatigue damage to the cover plate material. Especially in application scenarios such as electric vehicles, the battery may be subjected to external forces such as vibration and impact, further exacerbating the fatigue problem. 3. Impact resistance: Although aluminum alloys have good toughness, the cover may still crack or deform under extreme conditions (such as collision or fall), affecting the safety of the battery. Especially for covers with thin-walled designs, impact resistance is an important consideration. 4. Low-temperature brittleness: Some aluminum alloys may become brittle in low-temperature environments (such as below -40°C), resulting in a decrease in their mechanical properties. This is a potential risk for electric vehicles or energy storage systems used in cold areas. 5. Conductivity and resistance. Although aluminum alloys have good conductivity, their resistance is still relatively high compared to highly conductive materials such as copper. In high-current application scenarios, higher contact resistance will lead to increased heat generation, affecting the efficiency and life of the battery. In addition, fluctuations in contact resistance may also cause voltage drops and affect the stability of the battery.
[0004] Lithium battery electrolyte is mainly composed of organic solvents, and its pH value is generally between 5.5 and 6.5, which is acidic. Therefore, the corrosion resistance of the battery cover in an acidic environment is very important, which can greatly increase the life of the lithium battery. In the existing technology, the corrosion resistance of aluminum materials is improved by improving the process, but the mechanical properties are often lost, which cannot meet the needs of consumers.
[0005] Therefore, there is an urgent need for an aluminum material with high corrosion resistance for a cover plate of a new energy lithium battery and a preparation method thereof. Summary of the invention
[0006] The purpose of the present invention is to provide an aluminum material for a new energy lithium battery cover plate with high corrosion resistance and a preparation method thereof.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing an aluminum material for a new energy lithium battery with high corrosion resistance, comprising the following steps:
[0009] (1) Weigh the aluminum material components according to the following mass percentage ratio: Fe 1.21-1.84%, Si 0.12-0.28%, Mn 0.22-0.47%, Ca 0.01-0.05%, Ti 0.03-0.05%, Sr 0.02-0.07%, Cu 0.35-0.62%, Cr 0.08-0.24%, V 0.01-0.07%, and the balance is Al and unavoidable impurities;
[0010] (2) heating and melting the aluminum material components to obtain a melt, and adding a refining agent to perform refining under a nitrogen atmosphere to obtain an aluminum material melt;
[0011] (3) casting and rolling the aluminum material melt to obtain a cast-rolled coil;
[0012] (4) homogenizing the cast-rolled coil to obtain a semi-finished product;
[0013] (5) cold rolling the semi-finished product to a thickness of 1.5-2.0 mm to obtain a cold-rolled sheet strip;
[0014] (6) The cold-rolled sheet strip is annealed to obtain an aluminum material for a new energy lithium battery cover plate with high corrosion resistance.
[0015] Furthermore, in step (1), the mass percentage ratio of Fe, Mn and Cu is (1.3-1.5): (0.3-0.4): (0.5-0.6).
[0016] The present invention can improve the corrosion resistance of aluminum materials by carefully selecting the component types and compositions of aluminum materials. However, it is found that only when the mass percentage ratio of Fe, Mn and Cu is (1.3-1.5): (0.3-0.4): (0.5-0.6), can the aluminum materials maintain excellent mechanical properties and acid corrosion resistance at the same time. Analysis shows that under this condition, the formation of harmful phases can be better suppressed, the precipitation of fine dispersed phases can be promoted, and the strength and toughness of the material can be improved. The optimal ratio of Fe, Mn and Cu can change the electrochemical behavior of aluminum alloys, reduce their corrosion rate in acidic environments, improve electrochemical behavior, enhance the acid corrosion resistance of materials, optimize microstructures, and form uniform grain structures and fine second phase distributions.
[0017] Furthermore, the homogenization treatment in step (4) is specifically as follows: firstly heating to 460°C-480°C, keeping warm for 5-7h, then heating to 560°C-580°C, keeping warm for 17-19h.
[0018] Furthermore, the annealing treatment in step (6) is specifically as follows: heating to 450-470°C at a heating rate of 20-30°C / s and keeping warm for 4-6 hours, heating to 530-550°C at a heating rate of 20-30°C / s and keeping warm for 7-9 hours, heating to 570-590°C at a heating rate of 20-30°C / s and keeping warm for 11-13 hours, and then cooling to 60-80°C at a rate of 30-40°C / s.
[0019] The present invention can further optimize the mechanical properties and acid corrosion resistance of aluminum materials through specific homogenization and annealing conditions, and can also improve the electrical conductivity of aluminum materials. The homogenization treatment of the present invention can make the alloy elements fully diffuse in the matrix, eliminate component segregation, help to form a uniform microstructure, reduce the formation of harmful phases, and improve the overall performance of the material. Impurities and coarse second phases (such as β-Fe phase, CuAl2 phase, etc.) in aluminum alloys will scatter electrons, increase resistance, and reduce the electrical conductivity of the material; through homogenization and annealing, the content of these impurities and second phases can be reduced, thereby reducing the scattering effect on electrons and improving electrical conductivity.
[0020] Furthermore, in step (2), the refining agent is hexachloroethane, and the amount added is 0.25-0.3% of the weight of the melt.
[0021] Furthermore, in the step (2), the aluminum material component is heated and melted at 1500-1550°C.
[0022] Furthermore, in the step (3), the upper and lower plate surfaces have a cast-rolled coil with uniform grains of level 1. The grain size is checked by metallographic EBSD sampling of the cast-rolled coil. The particle size ratio at the surface layer 1 / 2 away from the center of the cast-rolled plate is 0.07-0.09, and the particle size ratio at the middle position of the cast-rolled plate is 0.15-0.18.
[0023] Furthermore, in step (5), the crown of the working roll of the cold rolling mill is controlled to be 0.01-0.03 mm, and the roughness Ra value is 0.16-0.18 μm.
[0024] Furthermore, in step (5), the total cold rolling deformation is controlled to be 60-70%.
[0025] The present invention provides an aluminum material for a new energy lithium battery cover plate with high corrosion resistance, which is prepared by the preparation method.
[0026] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0027] 1. The present invention can improve the corrosion resistance of aluminum materials by carefully selecting the component types and compositions of aluminum materials. However, it is found that only when the mass percentage ratio of Fe, Mn and Cu is (1.3-1.5): (0.3-0.4): (0.5-0.6) can the aluminum material maintain excellent mechanical properties and acid corrosion resistance at the same time.
[0028] 2. The present invention can further optimize the mechanical properties and acid corrosion resistance of aluminum materials and improve the electrical conductivity of aluminum materials through specific homogenization and annealing conditions. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] This embodiment provides an aluminum material for a new energy lithium battery cover plate with high corrosion resistance, and a preparation method thereof includes the following steps:
[0032] (1) Weigh the aluminum material components according to the following mass percentage ratio: Fe 1.45%, Si 0.24%, Mn 0.36%, Ca 0.04%, Ti 0.04%, Sr 0.05%, Cu 0.55%, Cr 0.13%, V 0.05%, and the balance is Al and unavoidable impurities;
[0033] (2) heating the aluminum material component to 1520° C. to melt and obtain a melt, and adding a refining agent to perform refining under a nitrogen atmosphere, wherein the refining agent is hexachloroethane and the amount added is 0.28% of the weight of the melt to obtain an aluminum material melt;
[0034] (3) Casting and rolling the aluminum material melt to obtain a cast-rolled coil with uniform grains on the upper and lower plate surfaces, and preparing an EBSD sample of the cast-rolled coil to check the grain size. The particle size ratio at the half distance from the surface to the center of the cast-rolled plate is 0.08, and the particle size ratio at the middle position of the cast-rolled plate is 0.16, thereby obtaining a cast-rolled coil;
[0035] (4) subjecting the cast-rolled coil to homogenization treatment, first heating the temperature to 470° C., keeping the temperature for 6 h, and then heating the temperature to 570° C., keeping the temperature for 18 h; and obtaining a semi-finished product;
[0036] (5) cold rolling the semi-finished product to a thickness of 1.8 mm, controlling the crown of the cold rolling mill working roll to 0.02 mm, the roughness Ra value to 0.17 μm, and controlling the total cold rolling deformation to 66% to obtain a cold-rolled sheet strip;
[0037] (6) The cold-rolled sheet strip is annealed as follows: the temperature is increased to 460°C at a heating rate of 25°C / s and kept at this temperature for 5 h, the temperature is further increased to 540°C at a heating rate of 25°C / s and kept at this temperature for 8 h, the temperature is increased to 580°C at a heating rate of 25°C / s and kept at this temperature for 12 h, and then the temperature is cooled to 70°C at a rate of 35°C / s to obtain an aluminum material for a new energy lithium battery cover plate with high corrosion resistance.
[0038] Example 2
[0039] This embodiment provides an aluminum material for a new energy lithium battery cover plate with high corrosion resistance, and a preparation method thereof includes the following steps:
[0040] (1) Weigh the aluminum material components according to the following mass percentage ratio: Fe 1.3%, Si 0.28%, Mn 0.4%, Ca 0.01%, Ti 0.05%, Sr 0.02%, Cu 0.6%, Cr 0.08%, V 0.07%, and the balance is Al and unavoidable impurities;
[0041] (2) heating the aluminum material component to 1550° C. to melt and obtain a melt, and adding a refining agent to perform refining under a nitrogen atmosphere, wherein the refining agent is hexachloroethane and the amount added is 0.3% of the weight of the melt to obtain an aluminum material melt;
[0042] (3) Casting and rolling the aluminum material melt to obtain a cast-rolled coil with uniform grains on the upper and lower plate surfaces, and preparing an EBSD sample of the cast-rolled coil to check the grain size. The particle size ratio at the half distance from the surface to the center of the cast-rolled plate is 0.08, and the particle size ratio at the middle position of the cast-rolled plate is 0.16, thereby obtaining a cast-rolled coil;
[0043] (4) subjecting the cast-rolled coil to homogenization treatment, first heating the temperature to 480° C., keeping the temperature for 7 h, and then heating the temperature to 560° C., keeping the temperature for 19 h; and obtaining a semi-finished product;
[0044] (5) cold rolling the semi-finished product to a thickness of 1.8 mm, controlling the crown of the cold rolling mill working roll to 0.02 mm, the roughness Ra value to 0.17 μm, and controlling the total cold rolling deformation to 70% to obtain a cold-rolled sheet strip;
[0045] (6) The cold-rolled sheet strip is annealed as follows: the temperature is increased to 450°C at a heating rate of 30°C / s and kept at this temperature for 6 h, the temperature is further increased to 550°C at a heating rate of 20°C / s and kept at this temperature for 7 h, the temperature is increased to 570°C at a heating rate of 30°C / s and kept at this temperature for 13 h, and then the temperature is cooled to 80°C at a rate of 30°C / s to obtain an aluminum material for a new energy lithium battery cover plate with high corrosion resistance.
[0046] Comparative Example 1
[0047] The difference between this comparative example and Example 1 is that the aluminum material components are weighed according to the following mass percentage ratio: Fe1.95%, Si0.34%, Mn0.16%, Ca0.04%, Ti0.01%, Sr0.08%, Cu0.25%, Cr0.03%, V0.05%, and the balance is Al and unavoidable impurities.
[0048] Comparative Example 2
[0049] The difference between this comparative example and Example 1 is that the aluminum material components are weighed according to the following mass percentage ratio: Fe1.15%, Si0.24%, Mn0.56%, Ca0.04%, Ti0.04%, Sr0.05%, Cu0.65%, Cr0.13%, V0.05%, and the balance is Al and unavoidable impurities.
[0050] Comparative Example 3
[0051] The difference between this comparative example and Example 1 is that the homogenization treatment is specifically: heating to 500° C. and keeping the temperature for 24 hours.
[0052] Comparative Example 4
[0053] The difference between this comparative example and Example 1 is that the homogenization treatment is specifically as follows: firstly heating to 430°C, keeping the temperature for 2h, then heating to 590°C, keeping the temperature for 22h;
[0054] Comparative Example 5
[0055] The difference between this comparative example and Example 1 is that the annealing treatment is specifically as follows: heating to 430°C at a heating rate of 15°C / s and keeping warm for 10 hours, heating to 570°C at a heating rate of 15°C / s and keeping warm for 5 hours, heating to 600°C at a heating rate of 15°C / s and keeping warm for 10 hours, and then cooling to 70°C at a rate of 50°C / s.
[0056] Comparative Example 6
[0057] The difference between this comparative example and Example 1 is that the annealing treatment is specifically as follows: heating to 560° C. at a heating rate of 25° C. / s, keeping the temperature for 25 h, and then cooling to 70° C. at a rate of 50° C. / s.
[0058] Performance Testing
[0059] The aluminum materials prepared in Examples 1-2 and Comparative Examples 1-6 were subjected to performance tests.
[0060] 1. Refer to GB / T228.1-2021 "Tensile test of metallic materials Part 1: Room temperature test method" for mechanical properties test.
[0061] 2. Conduct electrical conductivity test according to GB / T3956-2008;
[0062] 3. Corrosion resistance: The sample is sprayed with hydrochloric acid with a pH of 6 for 48 hours and allowed to stand for 12 hours. The sample is weighed and calculated before and after corrosion: the weight gain of corrosion products and the area fraction of white spots on the surface of the sample are counted. If the weight gain of corrosion products is ≤0.015% and the area fraction of white spots is ≤10%, it is qualified; if it does not meet the requirements, it will be recorded as unqualified.
[0063] The results are shown in Table 1.
[0064] Table 1 Performance test results
[0065]
[0066] From the above performance test results, it can be seen that Examples 1-2 have excellent mechanical properties, high electrical conductivity, and good acid corrosion resistance, especially Example 1 has the most outstanding comprehensive performance, which is mainly due to the synergistic effect of the components of the aluminum material and the preparation conditions.
[0067] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the composition of the aluminum material is changed, and it can be seen that the comprehensive performance is significantly reduced. In comparative example 2, the content of Fe, Mn and Cu is changed, and the mechanical properties and corrosion resistance are reduced. The homogenization treatment conditions of comparative examples 3-4 are changed, and the annealing treatment conditions of comparative examples 5-6 are changed, which will affect the mechanical properties, electrical conductivity and corrosion resistance of the aluminum material to varying degrees. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0068] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing an aluminum material for a new energy lithium battery with high corrosion resistance cover plate, characterized in that: The following steps are involved: (1) Weigh the aluminum material components according to the following mass percentage ratio: Fe 1.21-1.84%, Si 0.12-0.28%, Mn 0.22-0.47%, Ca 0.01-0.05%, Ti 0.03-0.05%, Sr 0.02-0.07%, Cu 0.35-0.62%, Cr 0.08-0.24%, V 0.01-0.07%, and the balance is Al and unavoidable impurities; (2) heating and melting the aluminum material components to obtain a melt, and adding a refining agent to perform refining under a nitrogen atmosphere to obtain an aluminum material melt; (3) casting and rolling the aluminum material melt to obtain a cast-rolled coil; (4) homogenizing the cast-rolled coil to obtain a semi-finished product; (5) cold rolling the semi-finished product to a thickness of 1.5-2.0 mm to obtain a cold-rolled sheet strip; (6) The cold-rolled sheet strip is annealed to obtain an aluminum material for a new energy lithium battery cover plate with high corrosion resistance.
2. The preparation process of the aluminum material for the new energy lithium battery high corrosion resistance cover plate according to claim 1 is characterized in that: The mass percentage ratio of Fe, Mn and Cu in step (1) is (1.3-1.5): (0.3-0.4): (0.5-0.6).
3. The preparation process of the aluminum material for the new energy lithium battery high corrosion resistance cover plate according to claim 1 is characterized in that: The homogenization treatment in step (4) is specifically as follows: firstly heating to 460°C-480°C, keeping the temperature for 5-7h, then heating to 560°C-580°C, keeping the temperature for 17-19h.
4. The preparation process of the aluminum material for the new energy lithium battery with high corrosion resistance cover plate according to claim 1 is characterized in that: The annealing treatment in step (6) is specifically as follows: heating to 450-470°C at a heating rate of 20-30°C / s and keeping warm for 4-6 hours, heating to 530-550°C at a heating rate of 20-30°C / s and keeping warm for 7-9 hours, heating to 570-590°C at a heating rate of 20-30°C / s and keeping warm for 11-13 hours, and then cooling to 60-80°C at a rate of 30-40°C / s.
5. The preparation process of the aluminum material for the new energy lithium battery with high corrosion resistance cover plate according to claim 2 is characterized in that: In the step (2), the refining agent is hexachloroethane, and the added amount is 0.25-0.3% of the weight of the melt.
6. The preparation process of the aluminum material for the new energy lithium battery high corrosion resistance cover plate according to claim 3 is characterized in that: In the step (2), the aluminum material component is heated and melted at 1500-1550°C.
7. The preparation process of the aluminum material for the new energy lithium battery high corrosion resistance cover plate according to claim 1 is characterized in that: In the step (3), the cast-rolled coil with uniform grains on the upper and lower plates is obtained. The grain size is checked by metallographic EBSD sampling of the cast-rolled coil. The particle size ratio at the half distance from the center of the surface layer to the cast-rolled plate is 0.07-0.09, and the particle size ratio at the middle position of the cast-rolled plate is 0.15-0.
18.
8. The preparation process of the aluminum material for the new energy lithium battery high corrosion resistance cover plate according to claim 5 is characterized in that: In the step (5), the crown of the working roll of the cold rolling mill is controlled to be 0.01-0.03 mm, and the roughness Ra value is 0.16-0.18 μm.
9. The preparation process of the aluminum material for the new energy lithium battery high corrosion resistance cover plate according to claim 5, characterized in that: In the step (5), the total cold rolling deformation is controlled to be 60-70%.
10. An aluminum material for a new energy lithium battery cover plate with high corrosion resistance obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Aluminum material for high-corrosion-resistance cover plate of new energy lithium battery and preparation method of aluminum material
CN114214545A
Casting aluminum alloy for near net shape casting of structural or non-structural components
CN117280057A
Material for new energy battery aluminum shell and manufacturing method thereof
CN117535564A
Aluminum alloy sheet for battery lid
TW200824171A
High-Strength Battery Cell Housing for Large-Format Round Battery Cells, Consisting of an Aluminium Alloy
US20240332679A1